Retained Primitive Reflexes and Potential for Intervention in Autistic Spectrum Disorders - Melillo, Robert; Leisman, Gerry; Machado, Calixto; Machado-Ferrer, Yanin; Chinchilla-Acosta, Mauricio; Kamgang, Shanine; Melillo, Ty; Carmeli, Eli (Frontiers in Neurology, 2022)
We provide evidence to support the contention that many aspects of Autistic Spectrum Disorder (ASD) are related to interregional brain functional disconnectivity associated with maturational delays in the development of brain networks. We think a delay in brain maturation in some networks may result in an increase in cortical maturation and development in other networks, leading to a developmental asynchrony and an unevenness of functional skills and symptoms. The paper supports the close relationship between retained primitive reflexes and cognitive and motor function in general and in ASD in particular provided to indicate that the inhibition of RPRs can effect positive change in ASD.